Pre-figurative practice and the educational leadership of Sir Alec Clegg in the West Riding of Yorkshire, England (1945–1974). (2nd October 2018) - Wood, Margaret; Pennington, Andrew; Su, Feng
ABSTRACT: This article recalls a time when local government infrastructure was strong and a Chief Education Officer's (CEO) vision could be realised across a region, in Clegg's case the West Riding of Yorkshire, one of the largest of the pre-1974 counties in England. It is timely to revisit Clegg's educational leadership and practice from 1945 to 1974, as a valuable source of learning, and challenge to the current ideologically-informed policy rhetoric which has undermined the framework of democratic educational decision-making. The authors identify four possible areas to learn from Clegg's work. Firstly, the need for CEOs or their modern-day equivalents or successors, to consider their potential as political and community leaders; secondly, Clegg's leadership style prefigures some of the recent discussion about the leadership of public services in uncertain times; thirdly a re-evaluation of administration and bureaucracy; and lastly the need for supportive partnerships to enable schools to thrive.